GLEDS (Gas Leakage Early Detection System) PROTOTYPE FOR EARLY DETECTION OF GAS LEAKS BASED ON MICROCONTROLLER ON MOTOR VEHICLES - Biantoro, Agung Wahyudi (Jurnal Teknik Mesin (Journal Of Mechanical Engineering), 2020)
Agung Wahyudi Biantoro                       Mechanical Engineering Department,  Universitas Mercu Buana, Jakarta.                               Jl. Meruya Selatan No. 1, Jakarta Barat.  Email : agung_wahyudi@mercubuana.ac.idPresent the need for efficient transportation is very important for modern human life. Various types of studies continue to be carried out to support the implementation of the use of Gas Fuel (CNG), to reduce dependence on fossil fuels. The use of BBG is considered more efficient and environmentally friendly than using fuel oil (BBM). However, thus, the use of CNG can hurt a negative impact on human safety and even cause considerable losses if it is not used carefully, especially if there is no known leakage from the tube and cause a fire to the vehicle. CNG gas that has a leak does smell so normal leakage is easily detected. However, if the leaky gas seeps into the engine, and the bottom of the bus or under the carpet, it will be difficult to detect. CNG gas is famous for its flammability so that the leakage of CNG equipment is at high risk of fire. Based on this description, the need for an early gas leak detection device using a microcontroller can monitor the presence of gas leaks in vehicles that can be observed directly through the LED screen in the form of a warning that can be placed on the cabin dashboard. From the above problems, the authors are interested in making a study by creating an innovation tool called GLEDS (Gas Leakage Early Detection System) in Microcontroller-Based Motorized Vehicles. The purpose of this study was to determine the condition of the design of the gas cylinder position in motorized vehicles and design the manufacture and GLEDS tool to detect gas leaks in motorized vehicles. Based on the whole system starting from the design and manufacture of GLEDS tools The conclusion is that the GLEDS gas leak detector can work well, this is indicated by the functioning of the tool when given butane gas. The buzzer sounds, the green LED lights up and displays graphical data on Android. Next, the sensor will detect a leak in the gas cylinder, if near the gas cylinder regulator there is really a butane gas content at a concentration of 280 ppm which then increases to 400 ppm. At a concentration of 300 ppm, the tool works well, with active buzzer alarms and LED lights. This GLEDS tool can be placed in the trunk of a car, close to gas cylinders of LNG four-wheeled motorized vehicles. Keywords: Gas Leak Detection, GLEDS, Arduino Uno, Microcontroller